ChemInform Abstract: "Quick and Click" Assembly of Functionalised Indole Rings via Metal‐Promoted Cyclative Tandem Reactions. Issue 18 (May 2015) - Capitta, Francesca; De Luca, Lidia; Porcheddu, Andrea
Abstract N‐Protected 2‐iodoanilines are smoothly transformed into indoles by a sequential Castro reaction using aldehydes instead of the commonly utilized alkynes.